2018
DOI: 10.1371/journal.pone.0198350
|View full text |Cite
|
Sign up to set email alerts
|

Wheat differential gene expression induced by different races of Puccinia triticina

Abstract: Puccinia triticina, the causal agent of wheat leaf rust, causes significant losses in wheat yield and quality each year worldwide. During leaf rust infection, the host plant recognizes numerous molecules, some of which trigger host defenses. Although P. triticina reproduces clonally, there is still variation within the population due to a high mutation frequency, host specificity, and environmental adaptation. This study explores how wheat responds on a gene expression level to different P. triticina races. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
(57 reference statements)
2
21
0
Order By: Relevance
“…It has been reported that UV-B radiation can induce virulence variation in Pst ( Shang et al, 1994 ; Huang et al, 2005 ; Wang et al, 2009 ; Zhao et al, 2019 ). Similarly, in studies on two other important pathogens— Puccinia triticina ( Neugebauer et al, 2018 ) and P . graminis f. sp.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been reported that UV-B radiation can induce virulence variation in Pst ( Shang et al, 1994 ; Huang et al, 2005 ; Wang et al, 2009 ; Zhao et al, 2019 ). Similarly, in studies on two other important pathogens— Puccinia triticina ( Neugebauer et al, 2018 ) and P . graminis f. sp.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that UV-B radiation can induce virulence variation in Pst (Shang et al, 1994;Huang et al, 2005;Wang et al, 2009;Zhao et al, 2019). Similarly, in studies on two other important pathogens-Puccinia triticina (Neugebauer et al, 2018) and P. graminis f. sp. tritici (Zhang et al, 2017), causing wheat leaf rust and wheat stem rust, respectively, it has also been reported that mutation may be the main mechanism of virulence variation of the two pathogens, thus resulting in the loss of wheat resistance and severe losses of wheat yield.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, such an approach that considers all elements of the infection procedure has not been applied in similar types of studies to date. Researchers have typically used two treatments (mock and pathogen treatments) [e.g., [35][36][37] or they have compared pathogen-infected plants with untreated plants [e.g., 38,39]. Thus, they were unable to assess the impact of the treatment procedure, which is particularly important for analyses of secondary metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to select the most suitable reference gene in different crops such as soybean (Libault et al 2008), rice (Maksup et al 2013), maize (Manoli et al 2012), chickpea (Garg et al 2010), pigeon pea (Sinha et al 2015) and wheat (Paolacci et al 2009) have been undertaken. However, limited reports are available for wheat during its interaction with Pt (Neugebauer et al 2018;Yanjun et al 2017;Casassola et al 2015;Scholtz and Visser 2013;Long et al 2010;Paolacci et al 2009). We evaluated five wheat housekeeping genes for their potential use in normalization of gene expression during the early stages of Pt infection using two statistical algorithms, BestKeeper and NormFinder.…”
Section: Methodsmentioning
confidence: 99%
“…However, understanding of the molecular mechanisms involved in T. aestivum-Pt interactions is very much sparse. More recently, a few studies were conducted to investigate wheat responses to Pt using RT-qPCR (Neugebauer et al 2018;Yanjun et al 2017;Casassola et al 2015;Manickavelu et al 2010).…”
Section: Introductionmentioning
confidence: 99%